Analysis of Education Service Quality at XYZ Institute with Servqual, PGCV, dan TRIZ Methods - Azzah Fadiyah; Kifayah Amar; Nurfaidah Tahir (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2023)
Abstract— Service quality is important for companies to maintain their business, including companies in the field of education services. Tutoring is a company engaged in the field of educational services. In the current era, many online tutoring has emerged. This resulted in offline tutoring having to improve its strategy to be able to compete in maintaining a business. XYX Institute is one of the offline tutoring institutions with the most students in Sulawesi. Amid intense competition with online tutoring, XYZ Institute needs to improve its strategy by improving the quality of its services. The purpose of this study is to measure the level of service quality at the XYZ Institute and provide recommendations for improvements that can be made to improve the quality of service. This study uses the servqual method to calculate the level of service quality, PGCV to determine the priority order of improvement and TRIZ which is used to analyze repair solutions. Based on the results of data processing, the level of service quality obtained is 96.022%. Then obtained 10 improvement priority attributes. The improvement solution obtained was to carry out several procurements, namely repairing toilet facilities, holding suggestion boxes on each floor, reading corners in the waiting room, and adding chairs and tables to the waiting room. In addition, it is necessary to increase the number of teachers and provide online registration services that are open longer, as well as add features for criticism and suggestions, consultations, learning reports, learning videos, and additional classes on the website.